Randomised controlled trial of parent groups for child antisocial behaviour targeting multiple risk factors: the SPOKES project. - Scott, S; Sylva, K; Doolan, M; Price, J; Jacobs, B; Crook, C; Landau, S (2010)
BACKGROUND: There is a pressing need for cost-effective population-based interventions to tackle early-onset antisocial behaviour. As this is determined by many factors, it would seem logical to devise interventions that address several influences while using an efficient means of delivery. The aim of this trial was to change four risk factors that predict poor outcome: ineffective parenting, conduct problems, attention deficit/hyperactivity disorder (ADHD) symptoms, and low reading ability. METHODS: A randomised controlled trial was carried out in eight schools in London, England. Nine hundred and thirty-six (936) 6-year-old children were screened for antisocial behaviour, then parents of 112 high scorers were randomised to parenting groups held in schools or control; 109 were followed up a year later. The intervention lasted 28 weeks and was novel as it had components to address both child behaviour (through the Incredible Years programme) and child literacy (through a new 'SPOKES' programme to help parents read with their children). Fidelity of implementation was emphasised by careful training of therapists and weekly supervision. Controls received an information helpline. Assessment of conduct problems was by parent interview, parenting by direct observation and child reading by psychometric testing. RESULTS: At follow-up parents allocated to the intervention used play, praise and rewards, and time out more often than controls, and harsh discipline less; effect sizes ranged from .31 to .59 sd (p-values .046 to .005). Compared to control children, whose behaviour didn't change, intervention children's conduct problems reduced by .52sd, (p < .001), dropping from the 80th to the 61st percentile; oppositional-defiant disorder (ODD) halved from 60% to 31% (p = .003). ADHD symptoms reduced by .44sd (p = .002), and reading age improved by six months (.36sd, p = .027). Teacher-rated behaviour didn't change. The programme cost pound2,380 ($3,800) per child. CONCLUSIONS: Effective population-based early intervention to improve the functioning of with antisocial behaviour is practically feasible by targeting multiple risk factors and emphasising implementation fidelity.